Heterogeneous mass balance of selected Glaciers in the Hindu Kush, Karakoram, and Himalaya between 2000 and 2018. Issue 1 (31st December 2023) - Hayat, Huma; Raup, Bruce; Muhammad, Sher; Liu, Shiyin; Khan, Romana; Baig, Siddique Ullah; Ahmad Tahir, Adnan
ABSTRACT: Glaciers in the Hindu Kush-Karakoram-Himalayas (HKH) are a major source of freshwater in the agriculture-dependent economy of Pakistan. In recent decades, mountain glaciers have been threatened by global warming. In this study, we estimated the Equilibrium Line Altitude (ELA) and geodetic mass balance of fifteen representative glaciers from Hunza (Karakoram), Chitral (Hindu Kush), and Astore (Himalaya) using Landsat satellite images and Advanced Space-borne Thermal Emission and Reflection Radiometer (ASTER) DEMs between 2000 and 2018. The climatic trends (temperature and precipitation) in the 19 years (1995–2013) time series of the three regions were assessed using the non-parametric Mann-Kendall test and Sen's Slope. The ELA of the observed glaciers except for two Atrak (Chitral) and Gulkin (Hunza) is shifted upward, while the mass balance indicates a heterogeneous pattern ranging from −0.23 ± 0.05 to −0.01 ± 0.015 m w.e a −1, −0.13 ± 0.05 to+0.17 ± 0.11 m w.e a −1 and −0.03 ± 0.02 to+0.23 ± 0.09 m w.e a −1 in Chitral, Hunza, and Astore basin, respectively. A significant or slight increasing or decreasing trend was found in the mean annual temperature, mean total precipitation, and mean discharge of the studied basins. This study will be a good contribution to understanding snow and glacier dynamics in HKH, the factors that influence them, and their interaction with the environment.